2011
DOI: 10.5578/tt.2332
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of knowledge about recent tobacco law number 5727 among our university students, academic and administrative staff

Abstract: In this study we investigated the level of knowledge and ideas of the university students and staff, about the last stage of Tobacco Law No. 5727, which came into force on 19 July 2009 in our country. This is descriptive questionnaire survey. Study's universe was consisting of the students 2009-2010 academic year studying in our universities and academic and administrative staff. A total of 2271 people were included the study. In our study, smoking prevalence was 21.3%. The prevalence for narghile smoking as 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…However, there have been studies showing that the prevalence of smoking is lower among college students in the medical field than among those in any other field. 7 , 18…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there have been studies showing that the prevalence of smoking is lower among college students in the medical field than among those in any other field. 7 , 18…”
Section: Discussionmentioning
confidence: 99%
“…Porém, há estudos mostrando que a prevalência do tabagismo é menor entre universitários da área médica do que entre os de qualquer outra área. 7 , 18…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A campaign for a "Smoke-Free Zone" was initiated with laws enacted in 2008 in Turkey and the application was expanded to include all indoor areas in 2009 (restaurants, cafes, bars, and cafes) (26). In research performed on university students and academic staff to evaluate the new tobacco laws, Gelen et al (27) showed that 85.7% of the university students and 93.1% of the academic staff supported this law. After the law was enacted, 68.1% of participants in this study reported that they enjoyed going to places where smoking is banned much more.…”
Section: Discussionmentioning
confidence: 99%